Análisis comunicacional en las relaciones intrafamiliares de los habitantes del sector el Seguro Social del cantón El Empalme, año 2021 - Vera Sánchez, Diana Mariana (2021)
The purpose of the research is to carry out a communicational analysis to know the situation of the intrafamily relations of the inhabitants of the Social Security sector of the El Empalme canton; Theoretical references on communication, the family: characteristics, types, functions and of course family functionality were preliminarily sought. A methodology based on a non-experimental design was applied, applying a qualitative and quantitative approach; Techniques (observation and surveys) and empirical methods (inductive, deductive and analytical) were used that will provide the means for data collection through observation, literature review and research, and surveys and interviews. The population is made up of the inhabitants of the canton extracted from the INEC website; the population segment was between 10 and 50 years old, an intentional sample of 109 inhabitants of the Social Security sector was taken. The results obtained allowed us to identify that the population, although they have communication with their family, this is not very fluid, in addition to having problems they do not have enough confidence to communicate what happens to their parents and family in general, the respondents also stated that they would like to participate in workshops and talks on family communication and thus be able to improve their intra-family relationships.